2011
DOI: 10.1007/s11661-011-0638-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Concurrent Straining on Phase Transformations in NiAl Bronze During the Friction Stir Processing Thermomechanical Cycle

Abstract: Equivalent strains up to a value of %2.7 were determined by evaluation of the shape changes of the phases in a duplex a(fcc)/b(bcc) microstructure formed ahead of the pin tool extraction site during the friction stir processing (FSP) thermomechanical cycle in a cast NiAl bronze alloy. Correlation of the local strains with volume fractions of the various microstructure constituents in this alloy shows that the concurrent straining of FSP results in acceleration of the a + b fi b reaction in the thermomechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…At "low" temperature, NAB undergoes intense plastic deformation during FSP, leading to grain refinement and microstructure uniformity. According to the previous literature, the refined grains and homogeneous microstructure can improve the mechanical properties of the NAB alloy [13,14]. The corrosion resistance of FSP NAB alloy is also enhanced by the refined grains [15].…”
Section: Introductionmentioning
confidence: 85%
“…At "low" temperature, NAB undergoes intense plastic deformation during FSP, leading to grain refinement and microstructure uniformity. According to the previous literature, the refined grains and homogeneous microstructure can improve the mechanical properties of the NAB alloy [13,14]. The corrosion resistance of FSP NAB alloy is also enhanced by the refined grains [15].…”
Section: Introductionmentioning
confidence: 85%
“…[6,[8][9][10]23,24] Briefly, multipass FSP was conducted using tools designed with a pin in the shape of a truncated cone and fabricated in Densimet 176. The tool shoulder diameter was 28.6 mm, the pin base diameter was 15 mm, the length was 12.7 mm, and tip diameter was 6.3 mm.…”
Section: Methodsmentioning
confidence: 99%
“…[8,9] Also, strains in the thermomechanically affected zone (TMAZ) surrounding the SZ can be estimated by evaluating the shape change of microstructure constituents. [10] Nevertheless, the rapid transients and steep gradients within the SZ, within the TMAZ, and into the base metal preclude direct correlation of the FSP thermomechanical cycle with local details of the microstructure, e.g., composition as well as grain size. However, annealing alone or uniform deformation under isothermal conditions will enable separate characterization of temperature and strain effects on the details of microstructure of the NiAl bronze material of the current investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the strengthening mechanisms of deformed NAB alloy have been investigated in many literatures [15,16]. Ni et al [17] found that dynamic recrystallization occurred in the stir zone during FSP.…”
Section: Introductionmentioning
confidence: 99%